Nutritional status at age 1 year in patients born with esophageal atresia: A population-based, prospective cohort study - Depoortere, Suzanne; Lapillonne, Alexandre; Sfeir, Rony; Bonnard, Arnaud; Gelas, Thomas; Panait, Nicoleta; Rabattu, Pierre-Yves; Guignot, Audrey; Lamireau, Thierry; Irtan, Sabine; Habonimana, Edouard; Breton, Anne; et al. (Frontiers in Pediatrics, 2022)
Objective Despite recent progress in caring for patients born with esophageal atresia (EA), undernutrition and stunting remain common. Our study objective was to assess nutritional status in the first year after birth with EA and to identify factors associated with growth failure. Study design We conducted a population-based study of all infants born in France with EA between 2010 and 2016. Through the national EA register, we collected prenatal to one-year follow-up data. We used body mass index and length-for-age ratio Z scores to define patients who were undernourished and stunted, respectively. Factors with P < .20 in univariate analyses were retained in a logistic regression model. Results Among 1,154 patients born with EA, body mass index and length-for-age ratio Z scores at one year were available for about 61%. Among these, 15.2% were undernourished and 19% were stunted at the age of one year. There was no significant catch-up between ages six months and one year. Patients born preterm (41%), small for gestational age (17%), or with associated abnormalities (55%) were at higher risk of undernutrition and stunting at age one year (P < .05). Neither EA type nor surgical treatment was associated with growth failure. Conclusion Undernutrition and stunting are common during the first year after birth in patients born with EA. These outcomes are significantly influenced by early factors, regardless of EA type or surgical management. Identifying high-risk patient groups with EA (i.e., those born preterm, small for gestational age, and/or with associated abnormalities) may guide early nutritional support strategies.